1998
DOI: 10.1212/wnl.50.5.1214
|View full text |Cite|
|
Sign up to set email alerts
|

Metrifonate treatment of the cognitive deficits of Alzheimer's disease

Abstract: The efficacy and safety of metrifonate, an acetylcholinesterase inhibitor, was evaluated clinically in patients diagnosed with mild to moderate Alzheimer's disease (AD). This was a prospective, 30-week, multicenter, double-blind, randomized, parallel group, dose-finding study, which included a 2-week screening period, a 12-week treatment period, and follow-up visits at 8 and 16 weeks post-treatment. Patients received placebo or metrifonate once daily. Metrifonate-treated patients received a loading dose of 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 11 publications
(2 reference statements)
5
77
0
2
Order By: Relevance
“…Metrifonate is a acetylcholinesterase inhibitor (AChEI) and increases ACh availability in the synapse in a more direct manner than 5-HT 6 antagonists (Cummings et al, 1998;Ringman and Cummings, 1999). Preclinical studies demonstrated that metrifonate improved age-impaired memory functions (spatial and nonspatial) (Dachir et al, 1997;Scali et al, 1997;van der Staay et al, 1996a) and scopolamine-induced impairments in water maze and passive avoidance tasks (Itoh et al, 1997;Riekkinen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Metrifonate is a acetylcholinesterase inhibitor (AChEI) and increases ACh availability in the synapse in a more direct manner than 5-HT 6 antagonists (Cummings et al, 1998;Ringman and Cummings, 1999). Preclinical studies demonstrated that metrifonate improved age-impaired memory functions (spatial and nonspatial) (Dachir et al, 1997;Scali et al, 1997;van der Staay et al, 1996a) and scopolamine-induced impairments in water maze and passive avoidance tasks (Itoh et al, 1997;Riekkinen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of cholinergic receptors shape neuronal excitability and synaptic throughput (Tai et al 2006) through multiple Ca 2+ -dependent processes (Gahwiler and Brown 1987;Tai et al 2006). Restoration of cholinergic function has been shown to rescue deficits on hippocampal-dependent tasks in aged rodent and mouse models of Alzheimer's disease (AD) (Disterhoft and Oh 2006), as well as in human AD patients (Cummings et al 1998;Morris et al 1998;Pettigrew et al 1998), and therefore is a potential target aimed at the rescue of early agerelated cognitive decline. …”
mentioning
confidence: 99%
“…Development of controlled-release physostigmine, 19,20 metrifonate, [21][22][23] velnacrine, 24,25 and eptastigmine [26][27][28] were discontinued because of unacceptable toxicities.…”
Section: Analysis Of Evidence Does Pharmacotherapy For Cognitive Symmentioning
confidence: 99%